Analisis Perubahan Watak Karakter Berdasarkan Struktur Cerita Lima Babak Dalam Film Yuni - Baskoro Aji Cahya; William Sanjaya (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
"Yuni" is a film that tells about a teenage girl who has big goal to continue her education to the university level. Yuni faces various inner problems that arise from herself and her environment related to myths and engagement. The film "Yuni" underwent a change in character traits which can be seen in the 5-act story structure. The purpose of this research is to find out the changes in the characters based on the 5-act story structure proposed by John Yorke. The research method used is a qualitative descriptive method using various theories and references to analyze changes in the character of the main character based on the five-act story structure. The theory used is the three-dimensional character theory proposed by Lajos Egri and the 5-act story structure theory proposed by John Yorke. From the research that has been done Yuni's character has changed in character in the form of a three-dimensional character that can be seen from the beginning and the end. The change in character can be completed with five rounds which include exposition, complication, climax, fall and disaster in the story in the film "Yuni". This concludes theme of the film “Yuni”, namely a woman who chooses freedom to achieve her dreams and fights against the myths of marriage in her environment.